2023
DOI: 10.1098/rsos.221322
|View full text |Cite
|
Sign up to set email alerts
|

Judgement bias may be explained by shifts in stimulus response curves

Abstract: Judgement bias, or ‘optimism’ and ‘pessimism’, has been demonstrated across many taxa, yet the cognitive mechanisms underlying this behaviour remain unclear. In an optimism paradigm, animals are trained to an association, and, if given a positive experience, behave more favourably towards ‘ambiguous’ stimuli. We tested whether this effect could be explained by changes to stimulus response gradients by giving bees a task where their response was tested across a wider gradient of stimuli than typically tested. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Here, such a "liking" effect as concentration increased did not produce significant changes in flight behaviour. While this is similar to what has been reported in experiments on cognitive bias tasks (37,38), the positive cognitive bias reported by these studies when bees are in a (supposedly) high hedonic state suggests that such a "liking" effect on flight behaviour is possible, perhaps in terms of trajectory (which betrays the search of alternatives within the environment). Importantly, by virtue of happening before reward consumption, any behavioural change in the flight characteristics of a bee flying toward a reward could be interpreted not as evidence of liking, but rather of the "expected pleasantness" of the reward (90).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, such a "liking" effect as concentration increased did not produce significant changes in flight behaviour. While this is similar to what has been reported in experiments on cognitive bias tasks (37,38), the positive cognitive bias reported by these studies when bees are in a (supposedly) high hedonic state suggests that such a "liking" effect on flight behaviour is possible, perhaps in terms of trajectory (which betrays the search of alternatives within the environment). Importantly, by virtue of happening before reward consumption, any behavioural change in the flight characteristics of a bee flying toward a reward could be interpreted not as evidence of liking, but rather of the "expected pleasantness" of the reward (90).…”
Section: Discussionsupporting
confidence: 89%
“…While these studies suggest a simple correlation between reward value and behavioural vigour, the relative importance of the reward intrinsic value and its value modulators is unclear. Moreover, two studies using judgment bias tasks have revealed that although an unexpected reward before a foraging flight reduces the sampling latencies of bees towards ambiguous stimuli, latency before choice to known options is unaffected (37,38). This suggests that changes in a bee's motivational state do not systematically translate into changes in behavioural vigour.…”
Section: Introductionmentioning
confidence: 99%
“…Insects' behavioral flexibility also plays a role in their possible affective responses to noxious or aversive stimuli, resulting in state-dependent judgment biases (Bateson et al, 2011;Deakin et al, 2018;Perry & Baciadonna, 2017;Procenko et al, 2023;Strang & Muth, 2023), neophobia (Cohen et al, 2015), and anxiety-like and depression-like behaviors in response to tests designed for eliciting anxiety and depression in mammals (reviewed in Gibbons et al 2022a). Further, we have documented throughout this paper the many ways insects respond flexibly, and sometimes site-and contextspecifically, to injuries.…”
Section: Contra Claimmentioning
confidence: 91%
“…Just as striking, brains of many sizes share a capacity to produce a number of seemingly complex abilities, such as numerical cognition, social learning, facial recognition, and various cognitive biases (all insects: Bateson et al, 2011;Bridges et al, 2023;Dacke & Srinivasan, 2008;Fellers & Fellers, 1976;Frisch & Seeley, 1967;Giurfa, 2012Giurfa, , 2015Giurfa et al, 2001;Howard et al, 2019;Leadbeater & Chittka, 2007;Mirwan & Kevan, 2013;Perry & Baciadonna, 2017;Perry & Barron, 2013;Strang & Muth, 2023;Tibbetts et al, 2021;Weise et al, 2022). Insects may even be capable of faster reversal learning than most vertebrates (evidence reviewed in Gibbons et al, 2022a).…”
Section: Thisbementioning
confidence: 99%
“…The impressive cognitive abilities of social insects have been (relative to solitary insects) well studied, hence our focus here. These abilities include: counting in bees (Dacke and Srinivasan 2008), numerical cognition that enables addition and subtraction in bees (Howard et al 2019), abstract concepts of same and different in wasps and bees (Giurfa et al 2001;Weise et al 2022), facial recognition in wasps (Tibbetts et al 2021), tool use in ants (Fellers and Fellers 1976), play-like behavior in bees and flies (Galpayage Dona et al 2022;Triphan and Huetteroth 2023), social information transfer (Frisch and Seeley 1967;Leadbeater and Chittka 2007;Mirwan and Kevan 2013;Bridges et al 2023), metacognitive-like processes (Perry and Barron 2013;Giurfa 2015), attention (Perry et al 2017), emotion-like states and judgment bias (Bateson et al 2011;Perry and Baciadonna 2017;Strang and Muth 2023), and self-medication (de Roode and Hunter 2019). There is an entire field of insect 'personality' (or, if you like, consistent individual behavioral differences) research (Jandt et al 2014).…”
Section: Behavioral and Cognitive Variationmentioning
confidence: 99%